TINJAUAN PERLINDUNGAN DATA PRIBADI ORANG YANG TELAH MENINGGAL DALAM PENGGUNAAN TEKNOLOGI DEADBOT ARTIFICIAL INTELLIGENCE DI INDONESIA - Yono Suherman,; Nur Arfiani, (Journal of Innovation Research and Knowledge, 2025)
The rapid development of artificial intelligence technology, which enables the creation of AI deadbots that mimic deceased individuals, has posed significant legal challenges regarding the protection of their digital footprints. This research aims to conduct a comprehensive analysis of the relevant legal frameworks in Indonesia to identify regulatory gaps and examine the protection of post-mortem rights. Using a normative juridical approach, supported by legislative and conceptual approaches, this study finds that the Law on Personal Data Protection (UU PDP) has not explicitly regulated the protection of post-mortem data, thus creating a significant legal vacuum. Nevertheless, the Copyright Law provides more substantial protection, particularly for moral rights that apply indefinitely and economic rights that are protected for 70 years after the creator's death. These findings indicate that Indonesia faces challenges in determining legal liability for AI and the inheritance of digital assets. Therefore, integrated and explicit legislation is needed to address the legal gaps and ensure the protection of citizens' rights in the digital era